Reframing Kindergarten Teacher Professionalism in Nurturing Deep Learning Experiences during Early Primary Education - Yuni Misrahayu; I Wayan Lasmawan; Desak Putu Parmiti; I Nyoman Tika (Asian Journal of Applied Education (AJAE), 2026)
This study examines the professionalism of kindergarten teachers in fostering deep learning experiences in early elementary school education. As the demands of developing high-level thinking skills and social-emotional competencies increase, early childhood teachers are required to carry out professional roles that are reflective, adaptive, and based on strong pedagogy. This research aims to reframe the professionalism of kindergarten teachers by examining the contribution of professional knowledge, pedagogical beliefs, and learning practices in supporting deep learning. The research uses a qualitative approach with multiple case study designs. Data was collected through classroom observation, semi-structured interviews, and analysis of learning documents, then analyzed thematically. The results of the study show that teachers with high professional flexibility, curriculum adaptability, and child-oriented pedagogical competence are more effective in creating a learning environment that encourages deep learning. Teacher professionalism is not only determined by formal qualifications, but also by the ability to integrate understanding of child development, responsive learning strategies, and designing meaningful learning. This study emphasizes the importance of strengthening cross-cultural competencies and reflective pedagogy in teacher education and early childhood education policies.